Concept and analysis of resilient frictional shear connector for coupled system. (1st June 2022) - Huang, Xiaogang; Liu, Ye; Sun, Xiaoyun
Abstract: Buildings designed using current seismic codes typically undergo significant structural damage and residual deformations under a design-level earthquake. To avoid this drawback in coupled structural systems, a novel resilient frictional shear connector (RFSC) that can improve both the energy dissipation capacity and structural resilience was proposed in this study. The RFSC is comprised of two T-shaped sections and two cover plates, which are clamped together by two arrays of pre-stressed high-strength bolts and disc springs. The equations governing the hysteretic loop of the coupled system using RFSC are first derived. Then three-dimensional finite element models were developed in Abaqus software for validating the RFSC and predicting the hysteretic response of the RFSC in the coupled system, respectively. Finally, a group of computational investigations of the RFFC in the coupled system subjected to static cyclic load are conducted to analyze the effect of varying key design variables such as the slope angle, the bolt preload, the spring stiffness and the friction coefficient. The parametric analysis confirmed the expected resilient behavior of the RFSC and explored the sensitivity of different parameters on the system responses such as stiffness, strength and equivalent damping ratio. Highlights: A novel resilient frictional shear connector (RFSC) was proposed for coupled systems. The RFSC consists of two T-shaped plates sandwiched by cover plates through bolts and disc springs. Theoretical and numerical analyses were conducted to elaborate the working mechanism of the RFSC.